Cheap as chips: Is a healthy diet affordable? - Christopher Snowdon (Institute of Economic Affairs (IEA), 2017)
It is widely believed that healthy eating is relatively expensive whereas 'junk food' is relatively cheap. This has led to an assumption that poor diets and obesity are directly caused by economic deprivation. Some studies have compared the price-per-calorie of various types of food. The inherent bias of this method has the effect of making many high-calorie food products appear cheap. For example, a low calorie yoghurt appears to be more expensive than an otherwise identical highcalorie yoghurt despite both products retailing at the same price. This report compares the price of food under two separate methodologies: direct comparisons of healthy and less healthy substitutes, and comparisons of healthy and less healthy products by edible weight. Prices were taken from two leading British supermarkets in November 2016. There is little difference between the price of regular food products and their healthier substitutes in most categories, such as baked beans, soft drinks, milk and bread. A few healthier options are more expensive (eg. brown rice, lean mince) while others are cheaper (eg. low-sugar breakfast cereals, yoghurt). White meat is significantly cheaper than red meat, but processed meat tends to be cheaper than fillets of meat. Most healthy substitutes cost the same, or are within 10 per cent (+/-), of the less healthy option. Measured by edible weight, healthier food in supermarkets tends to be cheaper than less healthy food. A wide range of fruit, vegetables and starchy carbohydrates are available at È 2.00 per kilogram. By contrast, the majority of less healthy products, such as ready-meals, chocolate, crisps and bacon, cost Ï 3.00, with very few available for less than 1 per kilogram. With the exception of fish, all of the food groups recommended in the UK government's Eatwell Guide can be bought for less than 2.00 per kilogram and a wide range of vegetables are available for less than 1.00 per kilogram. The recommendation of eating five portions of fruit and vegetables a day can be met for as little as 30p. The ingredients for a nutritious meal can be bought for significantly less than the cost of 'junk food', ready-meals and - by a wide margin - takeaway food. It is not the direct cost of less healthy food choices that drives their consumption. On the contrary, it seems that UK consumers are prepared to pay more for taste and convenience. Neither price nor nutritional quality are necessarily considered paramount by food shoppers. Since healthy food is generally cheaper than less healthy food, it is unlikely that taxes and/or subsidies would have a significant impact on dietary choices. Taxing food that is disproportionately consumed by people on low incomes in order to subsidise food that is disproportionately consumed by people on high incomes would be heavily regressive unless people on low incomes responded by changing their dietary habits dramatically, which is unlikely.
Keywords: H21; D03; D61; H21; D03; D61; 330; Food price; Nutritional behavior; Health; Great Britain; Lebensmittelpreis; Ernährungsverhalten; Gesundheit; Großbritannien